Pengaruh Dukungan Organisasi dan Komunikasi Interpersonal terhadap Komitmen Afektif melalui Kepuasan Kerja sebagai Variabel Intervening pada Karyawan bagian Pengemasan PT. Sido Muncul Semarang, Tbk - Hilda Atika Kusumawardhani; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2017)
The success of the organization in achieving the objectives that have been determined is determined by the success of the employees in carrying out its duties. These employees are ultimately the executor of activities within the organization and have an important role in efforts to achieve the goals of the organization. It is unfortunate when in reality the utilization of employees as human resources has not been optimal.The purpose of this research is to know the effect of organizational support and interpersonal communication to affective commitment through job satisfaction as intervening variable. Type of research used in this research is a type of research eksplanatory research. This research is aimed to find out the magnitude of relationship and influence between research variables. In this study the population is the employee of packaging PT. Sido Muncul Semarang. So it can be concluded that the sample to be taken at least 80 people with the reasons of time limitations, for that number of research samples to be researched as many as 100 people because it already meets the minimum sample amount of 80 people. In this research the sampling technique used is non probability sampling. This sampling technique is a sampling technique in a particular consideration to determine which population members will be selected as samples and data collected through questionnaires.The analysis used in this research is inferential analysis (test of validity and reliability test), coefficient of determination, cross table analysis, simple linear regression analysis, multiple linear regression analysis, t test, f test, and path analysis. The results of this research instrument testing using computer programming tool SPSS (Statistical Program for Social Science) For Windows version 19.The conclusion in this research is organizational support has an affect on to Job Satisfaction at packaging department employees PT. Sido Muncul Semarang. Interpersonal Communication affects Job Satisfaction at packaging department employees PT. Sido Muncul Semarang. Organizational Support has an affect on to Affective Commitment at packaging department employees PT. Sido Muncul Semarang. Interpersonal Communication affect on to Affective Commitment at packaging department employees PT. Sido Muncul Semarang. Job Satisfaction affect on to Affective Commitment at packaging department employees PT. Sido Mucul Semarang.Suggestions can be submitted for PT. Sido Muncul Semarang is to be more appreciate its employees especially on the packaging by giving rewards and punishment. Employees in achieving job targets should be maintained and improved performance and job satisfaction in order to arise the spirit and motivation of employees to be able to build the company better.